Malignant liver tumours. Issue 12 (December 2017) - Drake, Thomas M.; Harrison, Ewen M.
Abstract: The liver is commonly affected by both primary and metastatic malignancy. The surgical management of liver tumours must be carefully considered to ensure good oncological outcomes and to avoid serious complications of liver surgery. Primary tumours of the liver include hepatocellular carcinoma and cholangiocarcinoma. The resectability of primary liver tumours is dependent on thorough preoperative staging. Primary liver tumours pose a major global health burden, particularly in Asia and in countries affected by epidemic viral hepatitis. Metastatic disease commonly affects the liver and often hepatic resection in such circumstances provides the best chance of prolonging life and disease free survival. This review discusses recent advances, in addition to the epidemiology, diagnosis and management of both primary and secondary liver tumours.